Empathy, sex and fluid intelligence as predictors of theory of mind - Ibañez, Agustin Mariano (2013)
Individual differences in theory of mind (ToM) are affected by a variety of factors. We investigated the relationship between empathy, sex and fluid intelligence (FI) as predictors of ToM in a random probabilistic sample of secondary students. First, we explored whether sex, as well as high, average or low levels of empathy and FI affect ToM performance. Furthermore, we assessed the contribution of empathy, sex and FI in predicting ToM by using a path analysis. This method allows testing of causal models of directed dependencies among a set of variables. The causal dependencies of empathy, sex and fluid intelligence were confirmed and identified. In addition, the model confirmed the direct effect of empathy, sex and fluid intelligence on ToM; and the indirect effect of sex mediated by empathy. Thus, individual differences in ToM levels are partially attributable to sex, empathy and fluid intelligence variability, raising important considerations for clinical research as well as ToM's theoretical models of domain specificity. © 2012 Elsevier Ltd.